2019
DOI: 10.1177/0300060518813058
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of arnebin-1 in rats with nonalcoholic fatty liver disease

Abstract: Objective To examine the effects of arnebin-1 on nonalcoholic fatty liver disease (NAFLD) induced by a high-fat diet (HFD). Methods Male Sprague–Dawley rats were fed an HFD for 10 weeks and then treated with arnebin-1 at a dose of 5, 10 or 20 mg/kg/day by gavage for a further 12 weeks of a 22-week HFD. Peripheral blood and liver tissues were collected for biochemical and histopathological examination. The mechanisms of arnebin-1 on liver fibrosis and insulin resistance (IR) were determined by Western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Previous results from our laboratory ascertained that Qiyin demonstrates a substantial potential to alleviate the hepatic steatosis condition in rats with NAFLD, which was induced by the intervention of HFD. There is sufficient evidence that Qiyin possesses the capability to decrease CYP2E1, SREBP1 and SREBP2 protein expression levels in hepatocytes, thereby mitigating oxidative stress, ameliorating hepatocyte steatosis, and diminishing both inflammation and injury to the hepatocytes [ 17 , 18 ]. Previous clinical investigations have shown that the administration of this prescription confers not only a marked relief in clinical symptoms but also significantly regulates serum glutamic pyruvic transaminase (GPT), triglyceride (TG), cholesterol (TC), body mass index (BMI), and other related parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results from our laboratory ascertained that Qiyin demonstrates a substantial potential to alleviate the hepatic steatosis condition in rats with NAFLD, which was induced by the intervention of HFD. There is sufficient evidence that Qiyin possesses the capability to decrease CYP2E1, SREBP1 and SREBP2 protein expression levels in hepatocytes, thereby mitigating oxidative stress, ameliorating hepatocyte steatosis, and diminishing both inflammation and injury to the hepatocytes [ 17 , 18 ]. Previous clinical investigations have shown that the administration of this prescription confers not only a marked relief in clinical symptoms but also significantly regulates serum glutamic pyruvic transaminase (GPT), triglyceride (TG), cholesterol (TC), body mass index (BMI), and other related parameters.…”
Section: Introductionmentioning
confidence: 99%